All-optical gain-controlled bidirectional add-drop amplifier using fiber Bragg gratings - Kim, CH; Yoon, H; Lee, SB; Lee, CH; Chung, YC (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2000)
We demonstrate an all-optical gain-controlled bidirectional add-drop amplifier (BADA) module by using two fiber Bragg gratings (FBG's), The proposed amplifier module could suppress the power fluctuation of the surviving channels within 0.2 dB even when thirteen out of fourteen channels were added or dropped, In addition, there was no degradation in the receiver sensitivity when this module was used for the bidirectional transmission of wavelength-division-multiplexing (WDM) signals.